Vibrio parahaemolyticus and Vibrio vulnificus in vitro colonization on plastics influenced by temperature and strain variability - Leighton, Ryan E.; Correa Vélez, Karlen Enid; Xiong, Liyan; Creech, Addison G.; Amirichetty, Karishma P.; Anderson, Gracie K.; Cai, Guoshuai; Norman, R. Sean; Decho, Alan W. (Frontiers in Microbiology, 2023)
Marine bacteria often exist in biofilms as communities attached to surfaces, like plastic. Growing concerns exist regarding marine plastics acting as potential vectors of pathogenic Vibrio, especially in a changing climate. It has been generalized that Vibrio vulnificus and Vibrio parahaemolyticus often attach to plastic surfaces. Different strains of these Vibrios exist having different growth and biofilm forming properties. This study evaluated how temperature and strain variability affect V. parahaemolyticus and V. vulnificus biofilm formation and characteristics on glass (GL), low-density polyethylene (LDPE), polypropylene (PP), and polystyrene (PS). All strains of both species attached to GL and all plastics at 25, 30 and 35°C. As a species, V. vulnificus produced more biofilm on PS (p < 0.05) compared to GL, and biofilm biomass was enhanced at 25°C compared to 30° (p < 0.01) and 35°C (p < 0.01). However, all individual strains’ biofilm biomass and cell densities varied greatly at all temperatures tested. Comparisons of biofilm forming strains for each species revealed a positive correlation (r = 0.58) between their dry biomass weight and OD570 values from crystal violet staining, and total dry biofilm biomass for both species was greater (p < 0.01) on plastics compared to GL. It was also found that extracellular polymeric substance (EPS) chemical characteristics were similar on all plastics of both species, with extracellular proteins mainly contributing to the composition of EPS. All strains were hydrophobic at 25, 30 and 35°C, further illustrating both species’ affinity for potential attachment to plastics. Taken together, this study suggests that different strains of V. parahaemolyticus and V. vulnificus can rapidly form biofilms with high cell densities on different plastic types in vitro. However, the biofilm process is highly variable and is species-, strain-specific, and dependent on plastic type, especially under different temperatures.